Menopause, menstrual and reproductive history, and bone density in northern Italy. Issue 5 (October 1996) - Parazzini, F; Bidoli, E; Franceschi, S; Schinella, D; Tesio, F; La Vecchia, C; Zecchin, R
Abstract : STUDY OBJECTIVE: To analyse the relationship between menstrual and reproductive factors and the risk of low bone mineral density (BMD). DESIGN: This was a population based screening programme carried out between 1991 and 1993 among 1373 perimenopausal women in northern Italy by means of dual photon absorptiometry at the lumbar spine. MAIN RESULTS: BMD was strongly related to the age at menopause. In comparison with women reporting menopause below 45 years of age, the odds ratios (OR) of being in the lowest compared with the highest BMD tertile were 0.7 (95% confidence interval (CI) 0.3, 1.5) and 0.3 (95% CI 0.1, 0.8), respectively, in those with menopause at age 45-49 and above 50 years: the trend in risk was significant. Likewise, the risk of being in the lowest tertile increased with years since the menopause. Compared with women who reported they had undergone the menopause less than two years before interview, the OR of being in the lowest BMD tertile were 2.1 (95% CI 1.1, 4.3), 2.3 (95% CI 1.1, 5.0), and 5.7 (95% CI 2.5, 12.9) respectively in women who reported menopause 2-5, 6-9, and > or = 10 years earlier. The protective effect on bone density of late age at menopause was observed in different strata of years since menopause. Likewise, the increasing risk of a low BMD with increasing years since the menopause was evident in strata of different age at menopause. No relationships were observed between BMD and the age at menarche, characteristics of menstrual cycles, and the duration of menses. Likewise, no association emerged between reproductive history, including parity and age at first pregnancy, and BMD. CONCLUSIONS: In this Italian population the risk of being in the lowest BMD tertile decreased with increasing age at menopause and increased with years since menopause. No relationships emerged between BMD and other menstrual characteristics or reproductive factors.